Structural changes in the industry of Poland against the background of eastern European Union states - Gierańczyk, Wiesława; Rachwał, Tomasz (Wydział Nauk Geograficznych i Geologicznych UAM, 2012)
Industrial restructuring processes associated with the transformation of the system taking place in Poland and other countries of Central and Eastern Europe bring about structural changes in manufacturing intended to develop intellectually-intensive industries based on the implementation of the latest research and development (R&D) results. The purpose of this article is therefore to present changes in the role of industry in the economy of Poland based on its share in employment and gross value added in comparison with other eastern EU countries, as well as structural changes in the industrial sectors (NACE divisions). The comparison will assess the competitive position of Polish industry on international markets, particularly against the other states transforming their economies. The analysis will seek to establish to what extent the structural changes in Polish industry indicate positive effects of the country’s economic transformation.
Keywords: European Union; industry; Poland; restructuring processes; structural changes